Peran Keluarga dalam Pencegahan HIV/ AIDS di Kecamatan Purwokerto Selatan - Colti Sistiarani; Bambang Hariyadi; Munasib Munasib; Septi Maria Sari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
There are still many obstacles in prevention program of HIV and AIDS, especially for prevention program with family-based. Southern Purwokerto Subdistrict is in the red zone of HIV and AIDS spread in Banyumas District. The purpose of the study was to examine the role of families in preventing HIV and AIDS. This type of research was qualitative research through phenomenology method by seeing perception about individual action. Data collection was conducted through in-depth interviews to key informants that were husbands and wives informant. The main informants were 6 husbands and wives couples while the comparison informants were 3 informants for the source triangulation. Data analysis used content analysis. The results of this study illustrated that the couples already know about HIV/ AIDSinformation, how to spread HIV and AIDS, and how to prevent HIV and AIDS. The role of HIV prevention had not been done optimally either by husband and wife. Wife had no control over her husband about sexual behavior. Socialization on HIV/ AIDSprevention and family empowerment efforts was also not optimally implemented related to health education in preventing HIV/ AIDStransmission. The follow up of this research is the importance of efforts to disseminate information about HIV and AIDS to families and communities.